(untitled) (Global Journal of Medical Research, 2021)
This study investigated the microbial activity present in sliced and unsliced commercialized leaves of Gnetum africanum in the humid region of Abia State, Nigeria. This indigenous vegetable contains nutrients that encourage microbial growth, which if not properly handled in a hygiene environment may lead to proliferation of microorganisms. One hundred grams each of sliced and unsliced leaves of Gnetum africanum were obtained randomly from three different markets, these samples were homogenized in distilled water and analysis was carried out following standard microbiological methods.